2006
DOI: 10.1111/j.1365-294x.2006.02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare arctic‐alpine plants of the European Alps have different immigration histories: the snow bed species Minuartia biflora and Ranunculus pygmaeus

Abstract: Minuartia biflora and Ranunculus pygmaeus are circumarctic plants with a few isolated occurrences in the European Alps. We analysed amplified fragment length polymorphism (AFLP) and chloroplast DNA sequence data to unravel the history of their immigration into the Alps and to provide data on their circumpolar phylogeography. In spite of the similar ecological requirements of the two species, they exhibit strikingly different immigration histories into the Alps. In M. biflora, the Alpine populations are most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 34 publications
(41 reference statements)
9
111
1
3
Order By: Relevance
“…Studies of other autogamous pioneer species that typically occur in snowbeds have also reported low or absent genetic diversity across highly disjunctive ranges in the North Atlantic region. Virtually no detectable AFLP variation was found in Ranunculus pygmaeus (Schönswetter et al 2006) and Saxifraga stellaris (Westergaard et al 2008), or in the partly selfing Arabis alpina , and no isozyme variation was found in the clonal and selfing grass Vahlodea atropurpurea (Haraldsen et al 1991). During the final stages of the last glaciation, when the large ice sheets retracted and exposed open habitats, such snowbed species probably had favourable conditions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies of other autogamous pioneer species that typically occur in snowbeds have also reported low or absent genetic diversity across highly disjunctive ranges in the North Atlantic region. Virtually no detectable AFLP variation was found in Ranunculus pygmaeus (Schönswetter et al 2006) and Saxifraga stellaris (Westergaard et al 2008), or in the partly selfing Arabis alpina , and no isozyme variation was found in the clonal and selfing grass Vahlodea atropurpurea (Haraldsen et al 1991). During the final stages of the last glaciation, when the large ice sheets retracted and exposed open habitats, such snowbed species probably had favourable conditions.…”
Section: Resultsmentioning
confidence: 95%
“…Some species were able to maintain high levels of genetic diversity because they expanded broadfrontedly into the previously glaciated areas (Alsos et al 2009;Eidesen et al 2007). Others experienced repeated bottlenecks leading to reduced genetic diversity in the entire region, as populations were successively founded by a few individuals (leading-edge colonization; Schönswetter et al 2006). Although long-distance dispersal now is acknowledged as an important and relatively frequent migration process in plants Nathan 2006), it may be difficult for long-distance immigrants of pioneer species to establish and contribute to a gene pool once an area is already colonized (Hewitt 1999).…”
Section: Introductionmentioning
confidence: 99%
“…5). Similarities between populations of the Alps or eastern Alps and those of the Scandinavian mountain range are known among flowering plants, such as Minuartia biflora (Schönswetter et al 2006), Vaccinium uliginosum (Alsos et al 2005), and eastern Alps populations of Ranunculus glacialis (Schönswetter et al 2003). These studies sampled the entire Scandinavian mountain range relatively sparsely and did not find variation among different portions of the mountain range.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, species with disjunct arcticalpine distributions have been studied in phylogeographic (reviewed by Abbott and Brochmann (2003)) and biogeographic contexts (Tkach et al, 2008c;Tolmachev, 1960;Yurtsev, 1962). The connections between the Arctic and southern high mountain ranges, such as the Alps (Ronikier et al, 2012;Schönswetter et al, 2003Schönswetter et al, , 2006Winkler et al, 2012), Rocky Mountains (Weber, 1965) or Central Asian mountains (Hedberg, 1992), are relatively well understood, to the extent that specific postglacial migration routes of the populations have been inferred (e.g., Alsos et al, 2007;Gussarova et al, 2012;Schönswetter et al, 2003Schönswetter et al, , 2007. The Arctic and southern alpine regions are environmentally similar in some respects, such as having a short growing season and low mean annual temperature.…”
Section: Introductionmentioning
confidence: 99%